DEVELOPMENT OF THE ADMINISTRATION OF THE SUKAHAJI MANDIRI COMMUNITY OF SUKAHAJI FOOD GROUP GROUPS IN SUPPORTING ORDERLY ADMINISTRATION - Ida Marina; Adi Oksifa Rahma Harti; Sri Umyati; Dadan Ramdani Nugraha; Miftah Dieni Sukmasari; Dinar Dinar; Dede Salim Nahdi (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service is carried out at the Sukahaji Mandiri Community Food Barn (LPM). This service is one of the efforts for orderly administration in farmer groups with the aim of farmer groups understanding the benefits of administration, various types of administration and the steps for making group administration. This service activity was carried out on Thursday, January 27, 2022. Most of the income of the people of Sukahaji Village, Majalengka Regency, was obtained from rice farming. The role of farmer groups has an important role in improving the welfare of farmers, especially related to income. This is inseparable from the efforts made by the group in protecting its members. The success of a farmer group is reflected in the ability of administrative management. So this certainly plays an important role in the sustainability of farmer groups further in increasing group productivity. The services that have been carried out provide understanding and ability to manage administration, including the creation of member books, group activity books, guest books, meeting minutes, agenda books for incoming and outgoing letters, management books and financial administration. Keywords: Administration; Farmers; welfare.